Standardization of the Illinois Psycholinguistic Abilities Scale for diagnosing students with learning difficulties in the Palestinian environment - Albadawi, Bushra Izzat; Dakhlallah, Nijimeh Mahmood; Obaid, Mahmoud Sameer; Assia, Salam (Journal of Educational and Psychological Sciences, 2022)
This study aims to provide the Illinois psycholinguistic abilities test to diagnose students with learning difficulties and classify them in the lower basic grade according to the local Palestinian environment, so that it is ensured that the Illinois Psycholinguistic Abilities Scale has psychometric properties that allow it to be used in evaluating people with learning difficulties in the Palestinian environment. And to ensure that the global components of the scale match the Palestinian environment. To achieve this, the descriptive analytical approach was adopted. The study community consisted of students of the lower basic grade who are regular in public schools in Jerusalem suburb, whose ages range from (3 to 9 years). A prospective sample of 48 boys and girls between the ages of 4 to 5 years was carried out, and the legalization sample consisted of (202) boys and girls aged (3-9 years), drawn randomly. The study instruments are the Illinois psycholinguistic scale to measure learning difficulties and the Revan scale to measure learning difficulties. It was proven that the Illinois test has high validity, which was verified by the apparent validity indicators, and the consistency of the items from the correlation of the item's score with the total score of the test, the consistency of the paragraphs from the correlation of the paragraph degree with the total degree of the test, and the ramifications of the matrix of correlations function to extract the factorial validity between the tests or sub-domains of the total test, and the test had a good stability coefficient that can be trusted through The stability of the correctors, the half-segmentation method, corrected by the Spearman-Brown equation, and the stability of Alpha Cronbach, and thus the test achieved good psychometric properties of validity and stability that make it ready for use and application in the Palestinian environment. Based on the results, the Illinois scale is characterized by a high degree of validity and reliability, distinguishing it between normal children and children with learning difficulties, and it is suitable for use in the Palestinian environment. It is recommended that the study be conducted on a larger rationing sample.
Keywords: Learning difficulties; Illinois scale; psycholinguistic abilities; diagnosis; rationing; scale; test